Induction Chemotherapy‐Related Covert Cardiac Remodeling in Pre‐Autologous Hematopoietic Stem Cell Transplantation for Multiple Myeloma: A Retrospective Observational Study - Chang Dai; Weidong Lin; Fangzhou Liu; Xin Chen; Yuhan Chen; Yu Jiang; Jiaojiao Bai; Yidong Lv; Jianhong Zheng; Hai Deng; Xin Du; Shulin Wu; et al. (Cancer Medicine)
ABSTRACT Background Autologous hematopoietic stem cell transplantation (ASCT) has emerged as a cornerstone in multiple myeloma (MM) management, offering the prospect of prolonged disease control. However, the induction chemotherapy drugs required prior to ASCT carry cardiovascular toxicity (CVT), potentially leading to a range of cardiovascular complications. Methods and Results This retrospective observational study, conducted at Guangdong Provincial People's Hospital from January 2020 to December 2023, analyzed 47 of the initial 173 patients who met the criteria. The cohort, comprising 22 males (46.81%) and 25 females (53.19%), had a mean age of 55.68 ± 11.38 years. They underwent various induction chemotherapy regimens, receiving a median of 5 (4–6) cycles of the course over an average duration of 7.10 ± 2.46 months. Before ASCT treatment following induction chemotherapy, echocardiographic findings indicated reductions in left ventricular end‐systolic dimension, right atrial diameter, E‐wave velocity, E/e' ratio, and the E/A ratio. The latter altered from a pretreatment value greater than 1 to posttreatment less than 1, marking diastolic dysfunction emergence or aggravation in 51.06% of patients. The electrocardiographic data indicate a reduced heart rate and prolonged P‐wave duration and P‐R duration, with an increase in arrhythmia incidence to 19.15% following induction chemotherapy. Conclusion Induction chemotherapy, administered prior to ASCT in patients with MM, can lead to the emergence or aggravation of cardiac diastolic dysfunction and increase the incidence of arrhythmic events. Therefore, it is crucial to emphasize the importance of balancing the benefits and risks of induction chemotherapy to maximize its efficacy while minimizing CVT.